Rapid GNSS ambiguity resolution using dual frequency integer relationship constrained algorithm. Issue 336 (May 2014) - Feng, W.; Huang, D. F.; Zhou, L. T.; Zhang, X.; Yan, L.
Abstract : The accuracy of pseudorange is critical to fast ambiguity resolution (AR), especially for single epoch AR. To achieve rapid and reliable positioning with the dual frequency global navigation satellite system (GNSS) receivers for short baseline applications, we propose an integrated method called dual frequency integer relationship constrained ambiguity resolution (FirCAR). FirCAR reduces the required accuracy of pseudorange measurements in the AR procedure of each high elevation satellite. The ambiguities fixed by FirCAR are then added into the observation equation to improve the accuracy of the float ambiguity solution for the remaining measurements at relatively low elevation. Depending on the improved accuracy of the float ambiguities, fixing ambiguities becomes easier through a round-off and/or a search algorithm. On-the-fly (OTF) AR experiments were conducted for static and kinematic GPS observables over short baselines (<13 km). These experiments prove that FirCAR can effectively reduce the observation epochs required to resolve ambiguities, compared to commonly used methods, especially in conditions that are challenging for GPS (e.g. few satellites available, high multipath). More than 95% of the ambiguities can be solved with a single epoch observation using the proposed AR procedure.